If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(-2x+3)=15
We move all terms to the left:
-3(-2x+3)-(15)=0
We multiply parentheses
6x-9-15=0
We add all the numbers together, and all the variables
6x-24=0
We move all terms containing x to the left, all other terms to the right
6x=24
x=24/6
x=4
| x²-x=462 | | 17c+8=497 | | 4k-9-6k+6=-15 | | (2x-10)+90=180 | | X=9y=12 | | 5x=244 | | 12s=-600 | | 9=x/4-16 | | 15n+30=60 | | 17.j-36=104 | | 3b+4+4b+5=79 | | 24+2/3(t)=4/3(t-2) | | (7h-4)(h-8)= | | -12c=144 | | m=84 | | 3(5x+8)=24+15x | | 8(25+x)500=x37.50 | | 8=(3m=4)=200 | | 6.2+r=12.5 | | 8n+3+3n+2=49 | | 32=6m-8 | | 3x+3x+6x+7x=38 | | 4x2+-16x+3=0 | | 3.5z-1=4z-3 | | 8(25)+x500=x300 | | 10y-2y+7=103 | | X^3+4x^2-21+0=0 | | 8x-6-2x+12=30 | | -13x-18=135 | | 4.8+t=-8 | | -100=4(6p-7) | | 1+8x+9=-20+2× |